High field 3T magnetic resonance imaging: MR-anatomy evaluation of traumatic knee injuries - Anup Biswas; Asim De (International Journal of Medical Research and Review, 2016)
Background: MRI has high applicability to the knees, in comparison with other joints, and it provides excellent diagnostic capacity for evaluating lesions of different types, such as ligament, meniscal, tendon, bone and chondral injuries. MR imaging does not utilize ionizing radiation and therefore it is entirely safe; it is also noninvasive, painless, and allows acquisition of images in multiple planes without repositioning the patient. In addition, MR provides excellent spatial and contrast resolution of both intra- and extra-articular structures.Objective: The purpose of the study was to review the normal MR anatomy of the internal structures of knee joint and to study MRI appearances of various meniscal and cruciate ligament injuries of knee.Results: Knee injuries were more commonly encountered in males as compared to females. ACL was the most commonly injured ligament followed by tears of the menisci. Medial meniscal tears were twice as common as lateral meniscal tears. Vertical and complex tears are slightly more common than horizontal tears, which were predominantly seen in elderly population bearing degenerative changes. PCL tears and tears of the collateral ligaments were rare.Conclusion: Magnetic resonance imaging is a good, accurate and non-invasive modality for the assessment of menisci and ligamenteous injuries. High field 3 T MRI is unique in its ability to evaluate the internal structures of knee with exquisite detail. MRI is highly accurate in the diagnosis of tears of the menisci and cruciate ligaments and thus, it is increasingly used as a first line investigation in patients with soft tissue trauma to knee.